Glycoprotein synthesis: From glycobiological tools to tailor-made catalysts - Davis, B; Jones, J (Georg Thieme Verlag, 1999)
The synthesis of pure, well-defined glycoproteins is essential to the study of the host of biological processes that they mediate. The use of a combined site-directed mutagenesis and chemical modification strategy allows the site-selective synthesis of homogenous glycoproteins, the determination of precise structure-activity relationships and the design of new synthetic catalysts. This general and powerful method is reviewed in the context of existing preparative techniques and the wide-ranging applications of glycoproteins are highlighted.